Histopathological and cytological spectrum of lymphadenopathy: a window to preliminary diagnosis - Sona Goyal; Rupinder Kaur Brar; Sahil Sehgal (International Journal of Medical Research and Review, 2017)
Introduction: Lymphadenopathy is a common clinical presentation of patients attending outdoor patient departments. The etiology varies with a wide spectrum ranging from inflammatory causes on one end to malignant on the other. In the present study, cytological and relevant histopathological diagnoses were done in 200 cases received in Department of Pathology.Aims and objectives: The present study aimed to find out the percentage of various lesions of lymph node and their prevalence according to age group and sex of patients. It also correlated the histo-cytodiagnosis in cases where both histology and cytology were available and compared the results of present study with similar other studies.Materials and Methods: This study was carried out in the department of pathology, Govt. medical college, Patiala. It included 200 cases of lymphadenopathies, either from Rajindra hospital or from health centers nearby. The cases were selected randomly. Lymph nodes included were of neck region, axilla, groin, from the extremities and the internal (mediastinal, abdominal and retroperitoneal). Apart from haematoxylin and eosin (H & E) stain, special stains like Ziehl–Neelsen stain and giemsa stain were done wherever needed.Results: Out of 200 cases, 93 (46.5%) cases were of reactive hyperplasia. Females were affected more commonly than males. Tuberculosis occurred more in younger patients whereas metastases were more common in older age group. Axillary lymph node was the most common lymph node involved.Conclusion: Histopathology gave accurate and confirmatory results than cytology. Lymph node evaluation is an integral part of patient management.